2011
DOI: 10.1038/ajg.2011.112
|View full text |Cite
|
Sign up to set email alerts
|

Defective IL10 Signaling Defining a Subgroup of Patients With Inflammatory Bowel Disease

Abstract: Impaired IL10 signaling characterizes a subgroup of IBD patients, whereas the majority of children with severe IBD including EO forms normally produces and responds to IL10. Defective IL22 signaling may additionally impair intestinal epithelial clearance. Our data point out the complexity of IBD, which represent a group of distinct diseases with several pathogenetic abnormalities.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
151
2
4

Year Published

2012
2012
2018
2018

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 240 publications
(165 citation statements)
references
References 27 publications
6
151
2
4
Order By: Relevance
“…The compound heterozygous mutations impaired IL-10R1 signaling, but not IL-10 binding Although the dysfunction caused by the aforementioned homozygous mutation has been shown, the underlying molecular mechanism remains unknown 13,14 (Supplementary Table 2). In this study, after the demonstration of defective IL-10R function, we further investigated the molecular mechanism.…”
Section: Il-10r1 Mutations Impair Il-10 Signalingmentioning
confidence: 99%
See 1 more Smart Citation
“…The compound heterozygous mutations impaired IL-10R1 signaling, but not IL-10 binding Although the dysfunction caused by the aforementioned homozygous mutation has been shown, the underlying molecular mechanism remains unknown 13,14 (Supplementary Table 2). In this study, after the demonstration of defective IL-10R function, we further investigated the molecular mechanism.…”
Section: Il-10r1 Mutations Impair Il-10 Signalingmentioning
confidence: 99%
“…23 The correlation of a SNP of IL-10R1 with IBD was demonstrated in some ethnic populations but not in others. 21,24 Therefore, besides the discovery in European and Lebanese, 13,14 it is useful to examine the rare variants of IL-10R in neonatal-onset IBD in other populations. In this study we further identified such rare variant in the Han Chinese.…”
Section: Il-10r1 Mutations Impair Il-10 Signalingmentioning
confidence: 99%
“…Néanmoins, le dialogue entre hôtes et bactéries, initié lors de la colonisation intestinale à la naissance, est indispensable à la maturation de la l'intestin où ils acquièrent une activité très efficace de phagocytose tout en devenant producteurs d'IL-10 (interleukine 10). Cette cytokine anti-inflammatoire, clé dans le maintien de l'homéostasie intestinale [9,10], contribue à leur propre conditionnement et les rend tolérants aux signaux pro-inflammatoires induits par les motifs bactériens [8]. Ces macrophages peuvent ainsi éliminer les bactéries qui franchissent l'épithélium sans provoquer de réponse inflammatoire délétère.…”
Section: L'épithélium Intestinal Premier Rempart Contre Les Bactérieunclassified
“…This cytokine may act on different cell types, by supressing the anti-inflammatory response in various tissues. Moreover, IL-10 is thought to be the main molecule responsible for the response to inflammatory reactions, particularly to inhibit changes mediated by tumor necrosis factor-α (Cullinan et al, 2008;Begue et al, 2011). Its action inhibits the synthesis of proinflammatory cytokines and stimulates the proliferation and differentiation of cells specialized in the body's defense (Begue et al, 2011).…”
Section: Introductionmentioning
confidence: 99%